Writing in English for the Workplace - Edward Tosques (Electronica, 2006)
Writing in English for the Workplace is an eLearning work for the acquisition of profession-oriented writing skills in English. It consists of tutorials and interactive exercise materials on a variety of text types, as well as on all stylistic aspects related to writing. The text-types cover the four major areas of mass communications, business, research and technology. The work is being published in installments, of which the Interactive Grammar is the first. The others will be added at regular intervals, to form an interlocking whole. These interactive learning materials were programmed with Macromedia Authorware. To read them over the internet you must first download/install, free of charge, the appropriate Authorware Web Player.